Study of the Effect of Open Dimensions on Concrete Reinforced Beams Strengthened with Ferrocement - منصور نزيه; تريكية علي; حمود ذو الفقار (Latakia University Journal -Engineering Sciences Series, 2021)
Openings have a considerable negative effect on the behavior of reinforced beams. This paper presents a technique to improve the overall performance of concrete beams with openings. The proposed strengthening technique is called “ferrocement”, and it implements a fine metal mesh covered with cement mortar to envelop the beam. This technique is affordable and easy to apply. In order to study the effect of the ferrocement, a numerical simulation was carried out, using ABAQUS software, on 7 reinforced beams with square openings. The studied variables were: the dimensions of the openings taken as a ratio of the beam depth. It was found that the mid-span displacements were smaller in the beams strengthened with the ferrocement compared to the beams without ferrocement. Moreover, there was a significant increase in maximum shear stress values in the strengthened beams. Overall, the ferrocement improved the performance of concrete beams with openings.